A Study of Perception of the Importance of English Language Skills among Indonesian Hotel Employees - Stefanus Prima (UIR Press, 2022)
Conducting classes for English as a Specific Purpose such as in hospitality and tourism requires thorough needs analysis that serves the needs all stakeholders. However, most studies investigate the perceptions of students of hospitality or tourism major, while the perceptions of hotel employees are rarely investigated. This study is aimed at investigating Indonesian hotel employees (n = 77) perceptions towards various aspects of English skills. No statistical differences were found on the 15-item questionnaire responses based on gender, current job level, hotel stars, and current job departments. However, the results showed that listening and speaking skills are perceived as the most important, while spoken grammar is considered as the least important.